A BOOK REVIEW: THE NEW CRITICISM - Jonathan Moore (Soegijapranata Catholic University, 2011)
In his book The New Criticism, Indian author Munir explores the complicated critical perspective of the same name that developed by American and British writers of the 1920s through the 1960s. Rather than explore the motives or intent of the author of a text or using the text's social or historical context to attempt to explore it, New Criticism Critics focused exclusively on the text itself. Over time, such close reading resulted in its own unique critical process as well as perspective. Authors such as John Crowe Ransom, W.K.Wimsatt and Monroe Beardsley gave shape and definition to the major tenants of the perspective. Munir, over the course of eight chapters helps clarify both the ideas and the major works of several New Criticism writers.